IMPROVING STUDENT’S GRAMMER IN WRITING SHORT STORY THROUGH COLLABORATIVE LEARNING (A CASE STUDY OF ELEVENTH GRADE AT SMAN 1 BATANGAN) - Khudriyah, Ida; Suryani, Fitri Budi; Riyono, Ahdi (SIMPLE: International Journal of English Education, 2024)
Abstract: One of the language English components is writing. Writing is the ability to articulate and express ideas or emotions that arise in the mind in the form of words, phrases, and paragraphs. Throughout the writing process, some students have expressed that learning to write feels tedious and unimportant to them. When teaching writing, there are numerous strategies that must be employed to promote written communication among students. Collaborative learning  is a strategy that can be employed in pairs or groups and has been proven to be effective in addressing students' writing challenges. A short story is a type of concise fiction, considering the events portrayed, the content of the story, the number of characters, and the word count used. To write a short story students must have capable in grammer. This research aims to determine the influence of the collaborative learning to improve  students' grammer in writing short story  at eleventh grade students of SMAN 1 Batangan. The research used both qualitative and quantitative research. Some inferences that can be made in light of the research findings and the comments in section four are as follows: Incorporating collaborative learning into the classroom can boost students' interest and motivation while also helping them write better short stories. It is evident from the table analysis conducted before and after treatment that there was an improvement, going from 39% in cycle 1 to 87% in cycle 2. There is a 48% improvement.